Experiences of Tuberculosis in a Tarai Village, Nepal - Engelbrektsson, Ulla-Britt; Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2019)
In focus is the experience of being a Tuberculosis (TB) patient in the mid-west Tarai of rural Nepal. The information derives from a longitudinal qualitative study between 2005 to 2017 in one and the same community. The findings show few changes in the experience of being a TB patient. The availability of anti-TB medicine free of cost within the government health services was greatly appreciated. The cause of TB, ways and means of transmissions, and the need for preventive measures, however, were not well understood. In the case of Child-TB, the expectation of numerous visits to the government treatment centre for the picking up of medicines was a strong deterrant. In consequence, most child-TB cases were diagnosed and treated within the private sector. The distribution system of the medicines, particularly within the government system, clearly added to the burden of being a TB patient and much would have been gained had the arrangement been more patient-friendly, a difference which most likely had also resulted in more children being treated within the public services rather than within the money-geared private sector. Various misunderstandings about the cause/s of the disease need to be addressed. And, much would be gained was the central directive of “patient support”, truly implemented and was a true “two-way communication” to take place.